Characterizing the nature and importance of lava-sediment interactions with the aid of field outcrop analogues. (June 2021) - Famelli, Natália; Millett, John M.; Hole, Malcolm J.; Lima, Evandro F.; Carmo, Isabela de O.; Jerram, Dougal A.; Jolley, David W.; Pugsley, Jessica H.; Howell, John A.
Abstract: The emplacement of lava flows into poorly consolidated sediments during volcanism can lead to a wide range of lava-sediment interaction processes. Understanding these processes and their products is critical for appraising reservoir quality and connectivity in both intra- and sub-volcanic prospectivity settings. This study investigates the nature of lava-sediment interactions during the onset of magmatism in sedimentary basins with the aid of field outcrops in the Paraná-Etendeka Igneous Province (Brazil), Mull Lava Field (UK), and Midland Valley Basin (UK). Both subaerial and invasive lava flows were identified with associated features ranging from peperites, loading structures, pillow-like peperites, rootless cones, and lavas with sharp contacts. Density contrasts between liquid magma and unconsolidated sediments make lava invasion a predictable phenomena in such environments, however, variations in sediment properties such as water saturation, porosity and cohesion may effectively restrict the process of invasion, the degree of loading and more dynamic processes leading to peperite and pillow-like peperite. Surface outcrop analogues form a key component to understand the potential impact of volcanism and magma-sediment interactions on non-volcanic reservoir rocks located proximal to the basalt-sediment transition. The intimate mixing of magma with sediment is generally restricted to a few meters from the lava-sediment contact, with an associated minor impact on reservoir quality. However, the process of lava invasion may extend this impact further and may lead to partial or complete compartmentalization of associated reservoir units and may additionally impact correlation at the detailed reservoir level. Highlights: Characterizing lava-sediment interaction facies from Paraná-Etendeka Igneous Province, Midland Valley Basin, and Isle of Mull. Use of high resolution 3D virtual outcrop models to capture and help characterize key lava-sediment facies. Appraisal of lava-sediment interaction processes operating during volcanism in active sedimentary basins. Discussion of the range of factors responsible for interaction types, and their implication for prospective petroleum systems.